Long-Term Results of Tibialis Anterior Tendon Transfer for Relapsed Idiopathic Clubfoot Treated with the Ponseti Method: A Follow-up of Thirty-seven to Fifty-five Years. (7th January 2015) - Holt, Joshua B.; Oji, David E.; Yack, H. John; Morcuende, Jose A.
Abstract : Background: Relapse of idiopathic clubfoot deformity after treatment can be effectively managed with repeat casting and tibialis anterior tendon transfer during early childhood. We evaluated the long-term effects on adult foot function after tibialis anterior tendon transfer for relapsed idiopathic clubfoot deformity during childhood. Methods: Thirty-five patients (sixty clubfeet) in whom idiopathic clubfoot was treated with the Ponseti method from 1950 to 1967 were followed. At an average age of forty-seven years (range, thirty-seven to fifty-five years), the patients underwent a detailed musculoskeletal examination, radiographic evaluation, pedobarographic analysis, and surface electromyography (EMG). They also completed three quality-of-life patient questionnaires. Results: Fourteen patients (twenty-five clubfeet, 42%) had required repeat casting and tibialis anterior tendon transfer in childhood for relapsed clubfoot deformity after initial casting and served as the study group. Twenty-one patients (thirty-five clubfeet, 58%) were successfully treated with initial casting without relapse (the reference group). No patient in either group had subsequent relapse or required additional operative intervention associated with clubfoot deformity. The mean ankle dorsiflexion was similar between the groups. Radiographically, the tendon transfer group showed a smaller mean anteroposterior talocalcaneal angle and slightly more talar flattening than the reference group with no associated clinical differences. Peak pressures, total force distribution, and surface EMG results were not significantly different between the groups. Outcome questionnaires demonstrated no significant difference between the groups. Conclusions: Tibialis anterior tendon transfer is very effective at preventing additional relapse of deformity without affecting long-term foot function of patients with idiopathic clubfoot. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.